Strengthening Families: How Family Support Shapes the Quality of Life for Children with Intellectual Disabilities - Anggi Kusuma; Rini Papuli; Lisbet Octovia Manalu (Health Research Journal of Indonesia, 2026)
Children with special needs are children who are at risk of experiencing chronic diseases, developmental disorders, emotional disorders, abnormalities or physical disabilities and require more health services than children in general. Family support is needed as a supporter and to help the quality of life of these children to continue to be able to carry out their activities with their abilities supported by the family. This type of quantitative research uses a cross-sectional approach. The population in this study were all parents who have children with special needs at the Mesuji Regency State Special School with a sample of 84 respondents using a total sampling technique. This study was conducted in December 2022 at the Mesuji Regency State Special School. The results of the study showed no significant relationship between the dimensions of family support and the quality of life of children with special needs. Family support in the form of providing information and social support should be a priority support given to families with children with special needs.